The alpha‐7 nicotinic acetylcholine receptor agonist GTS‐21 engages the glucagon‐like peptide‐1 incretin hormone axis to lower levels of blood glucose in db/db mice. Issue 7 (7th April 2022) - Meng, Qinghe; Chepurny, Oleg G.; Leech, Colin A.; Pruekprasert, Napat; Molnar, Megan E.; Collier, James Jason; Cooney, Robert N.; Holz, George G.
Abstract: Aim: To establish if alpha‐7 nicotinic acetylcholine receptor (α7nAChR) agonist GTS‐21 exerts a blood glucose‐lowering action in db/db mice, and to test if this action requires coordinate α7nAChR and GLP‐1 receptor (GLP‐1R) stimulation by GTS‐21 and endogenous GLP‐1, respectively. Materials and Methods: Blood glucose levels were measured during an oral glucose tolerance test (OGTT) using db/db mice administered intraperitoneal GTS‐21. Plasma GLP‐1, peptide tyrosine tyrosine 1‐36 (PYY1‐36), glucose‐dependent insulinotropic peptide (GIP), glucagon, and insulin levels were measured by ELISA. A GLP‐1R–mediated action of GTS‐21 that is secondary to α7nAChR stimulation was evaluated using α7nAChR and GLP‐1R knockout (KO) mice, or by co‐administration of GTS‐21 with the dipeptidyl peptidase‐4 inhibitor, sitagliptin, or the GLP‐1R antagonist, exendin (9‐39). Insulin sensitivity was assessed in an insulin tolerance test. Results: Single or multiple dose GTS‐21 (0.5‐8.0 mg/kg) acted in a dose‐dependent manner to lower levels of blood glucose in the OGTT using 10‐14 week‐old male and female db/db mice. This action of GTS‐21 was reproduced by the α7nAChR agonist, PNU‐282987, was enhanced by sitagliptin, was counteracted by exendin (9‐39), and was absent in α7nAChR and GLP‐1R KO mice. Plasma GLP‐1, PYY1‐36, GIP, glucagon, and insulin levels increased in response to GTS‐21, but insulin sensitivity, body weight, and food intake were unchanged. Conclusions: α7nAChR agonists improve oral glucose tolerance in db/db mice. This action is contingent to coordinate α7nAChR and GLP‐1R stimulation. Thus α7nAChR agonists administered in combination with sitagliptin might serve as a new treatment for type 2 diabetes.